The effect of DNA methylation on bumblebee colony development - Pozo, María I.; Hunt, Benjamin J.; Van Kemenade, Gaby; Guerra-Sanz, Jose M.; Wäckers, Felix; Mallon, Eamonn B.; Jacquemyn, Hans (BMC genomics, 2021)
Although around 1% of cytosines in bees' genomes are known to be methylated, less is known about methylation's effect on bee behavior and fitness. Chemically altered DNA methylation levels have shown clear changes in the dominance and reproductive behavior of workers in queen-less colonies, but the global effect of DNA methylation on caste determination and colony development remains unclear, mainly because of difficulties in controlling for genetic differences among experimental subjects in the parental line. Here, we investigated the effect of the methylation altering agent decitabine on the developmental rate of full bumblebee colonies. Whole genome bisulfite sequencing was used to assess differences in methylation status. Our results showed fewer methylated loci in the control group. A total of 22 CpG loci were identified as significantly differentially methylated between treated and control workers with a change in methylation levels of 10% or more. Loci that were methylated differentially between groups participated in pathways including neuron function, oocyte regulation and metabolic processes. Treated colonies tended to develop faster, and therefore more workers were found at a given developmental stage. However, male production followed the opposite trend and it tended to be higher in control colonies. Overall, our results indicate that altered methylation patterns resulted in an improved cooperation between workers, while there were no signs of abnormal worker dominance or caste determination.